Elucidation of antiproliferative mechanism of dendrophthoe pentandra methanolic extract on breast cancer cells (MCF-7) - Zainuddin, Nik Aina Syazana Nik (2016)
Cancer is one of the major causes of death, worldwide. The ultimate goal of cancer treatment is to remove the malignant cells completely without harming healthy cells. There is an urgency to find a safe and highly effective treatment for cancer disease and it remains a big challenge nowadays. Throughout medical history, herbal plants have been shown to be one of valuable sources in combating cancer such as Dendrophthoe pentandra (DP). DP or Mistletoe is a semi-parasitic plant with traditional claims for anticancer property. However, the mechanism underlying anticancer activity is unclear and need to be explored. Therefore, DP was selected in order to evaluate its antiproliferative activity and mode of cell death in cancer treatment. The extraction of DP leaves were carried out using methanol (DPME) by maceration technique. Phytochemicals compound present in DPME were screened and quantified. Tannin is the most abundance phytochemical present in DPME. The antiproliferative activities of DPME towards HeLa, HepG2, MCF-7, U-2 OS and MDA-MB-231 cell lines have been examined by MTT Assay and IC50 values were obtained. MCF-7 cells showed the most effective growth inhibition with lowest IC50 value upon treatment with DPME. The cytotoxicity activities towards normal kidney MDCK and normal fibroblast L-929 cells were evaluated to determine the cytoselectivity property of DPME. The nuclear staining by Hoechst 33258 displayed the chromatin condensation, fragmented nuclei and formation of apoptotic bodies upon treatment with DPME according to certain period of time. Flowcytometric analysis using Annexin V/PI double staining has confirmed that DPME-treated MCF-7 arrested cell cycle distribution at G1/S phase and induced apoptosis. The mechanism of action was further confirmed by determination of protein involved in apoptosis pathway; Bcl-2, Bax, p53 and cytochrome C. The results found out that the increased of p53 was followed by an increment of pro-apoptotic, Bax and decreased of anti-apoptotic, Bcl-2. Activation of Bax and inactivation of Bcl-2 triggered release of cytochrome C which leads to apoptosis event. In conclusion, DPME demonstrated antiproliferative activity in MCF-7 cells by induction of apoptosis. Therefore, DP has a promising approach for breast cancer treatment.